Plane-symmetric mesonic viscous fluid cosmological model - Singh J.K.; Shri R. (My University, 2025)
Exact nonstatic solutions to Einstein field equations are obtained for the plane symmetric spacetime filled with viscous perfect fluid in the presence of attractive scalar fields. Some physical and geometrical properties of the model are studied. The solutions characterize strong interaction of elementary particles.